The efforts to increase the attractiveness of Bingkon Kakao MSME products through redesign of chocolate bar packaging - Muttaqien, Muhammad; Nafza, Gisellya Noorrahma Shalihatan (Community Empowerment)
Natural resources are one of the things that can be utilized and processed to be used as a source of economic income for large industries, SMEs and individuals. Nglegi is one of the hamlets in the Patuk sub-district, Gunung Kidul Regency, DI Yogyakarta which has the potential for cocoa plants to spread in almost every citizen's yard. Cocoa (Theobroma cacao L. Cocoa) is a type of plant that is very popular with its processed fruit, one of which is chocolate. The people of Nglegi who are members of the Ngudi Mulyo farmer group make processed cocoa beans with the Bingkon Kakao brand as a source of income. Bingkon Cocoa itself already has processed types such as cocoa powder, chocolate rengginang and chocolate bars. However, based on observations, the production of chocolate, especially chocolate bars, the appearance of the packaging design was less attractive, thereby reducing the attractiveness of potential buyers. This service goes through three stages, namely preparation, implementation, and evaluation. The result of the service is the creation of a new design for the Bingkon Kakao chocolate bar packaging which is expected to be an attraction for product sales.